Exposing One-Stop Platform Stock Investment Phenomenon: The Role of Generated Content, Fear of Loss, and Financial Literacy - Akmando, Luthfi Jovan Wandy; Adiwijaya, Karto (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The one-stop platform of stock investment has a positive effect on technological developments in the world of stock investment. That triggers changes in investor behavior in buying stock. This research investigates the influence of the